Korelasi Fungsi Rumah Bagi Orang Kristen Dan Gereja - Lengkong, Samuel; Wulus, Mega Sinta (JURNAL LUXNOS, 2023)
Abstract: When dealing with the Covid-19 pandemic, churches are faced with new challenges. In the midst of these conditions, there were pro and contra responses among God's servants or congregations regarding worshiping at home, where some groups understood that Carrying out worship at home is an indication of a lack of faith, for fear of the Covid-19 pandemic. Meanwhile, the other group understands it as wisdom in the midst of the existing conditions and follows the government's direction as part of obedience to God's Word towards the government. Qualitative research methods were used in this research, with a literature study approach, researchers analyzed a number of data in the form of concepts or theories, literature and journals were analyzed by exegesis according to the research topic. This research aims to find and reveal the understanding of the Christian family home as a church. The results of this study are that the Christian family home as a church is very relevant to be applied in the midst of the covid-19 pandemic and in all ages with various challenges which are in principle the same as the covid-19 pandemic situation, even without the challenges of the times, every Christian family should carry out activities and church activities in their respective homes, because the home of a Christian family is an ark of salvation. Abstrak: Pada saat menghadapi situasi pandemik Covid-19, gereja-gereja mendapat tantangan baru. Di tengah kondisi tersebut muncul tanggapan pro dan kontra di kalangan para hamba Tuhan ataupun jemaat mengenai beribadah di rumah. Sebagian kelompok memahami bahwa melaksanakan ibadah dirumah adalah indikasi kurangnya iman, karena takut dengan pandemic Covid-19. Sedangkan kelompok lainnya memahami sebagai hikmat di tengah kondisi yang ada dan mengikuti arahan pemerintah sebagai bagian ketaatan pada Firman Tuhan terhadap pemerintah. Dalam penelitian ini perlu melihat bagaimana korelasi fungsi dari rumah bagi orang Kristen. Metode penelitian kualitatif digunakan dalam penelitian ini, dengan pendekatan studi literatur peneliti menganalisis sejumlah data dalam bentuk konsep atau teori, literatur dan jurnal dilakukan analisis dengan mengeksegesis sesuai topik penelitian. Penelitian ini bertujuan untuk dapat menemukan dan mengungkapkan pemahaman rumah keluarga Kristen sebagai gereja. Hasil penelitian ini adalah bahwa rumah keluarga Kristen sebagai gereja menjadi sangatlah relevan diterapkan di tengah pandemic covid-19 dan dalam segala zaman dengan berbagai tantangan yang pada prinsipnya sama dengan situasi pandemik covid-19, bahkan tanpa ada tantangan zaman pun sudah seharusnya setiap keluarga Kristen melaksanakan kegiatan dan aktivitas gereja di dalam rumah masing-masing, karena rumah keluarga Kristen merupakan bahtera keselamatan.